Dinamika Perempuan Berpolitik: Strategi Pengembangan Partai Keadilan Sejahtera di Era Reformasi - Mochamad Parmudi; Tulus Warsito; Sidik Jatmika (Sawwa: Jurnal Studi Gender, 2018)
Partai Keadilan Sejahtera (PKS) is a unique and phenomenal party, it was born from the womb of a social-religious movement named Jama'ah Tarbiyah which later morphed into an Islamic political party. The PKS social base is a middle-class, educated and young Muslim community. This research explores the strategy of developing PKS in Kebumen District from 1999 to 2014 in the dynamics of Indonesian Islamic politics. This research reveals the unique phenomenon of PKS Kebumen's role in an electoral manner in the distribution of votes and seats in the Dewan Perwakilan Rakyat Daerah (DPRD). The method of approach uses phenomenological studies. The results of this study are that PKS was born of an ideology or Islamic religious thought. His birth was acceptable to the community because PKS approached the community through collective actions such as; majlis ta'līm, social services, natural disaster assistance, channeling financial loan funds, establishing school buildings, and places of worship.